(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Social media platforms have become the new essentials of communication, entertainment, and information sharing. Artificial Intelligence has played a transformative role in their evolution. This research explores how AI enhances social media platforms through personalizing content feeds, detecting fake news, and improving user engagement. Personalization algorithms like collaborative filtering and machine learning models tailor content to user behavior, which raises the satisfaction level of users and enhances interaction. Another critical role that AI plays in combating the increasingly prevalent problem of fake news is through employing techniques such as NLP and machine learning for detecting and eliminating false information. Other AI-based engagement strategies include recommendation systems and automated chatbots that enhance user retention and participation. However, it also faces issues like privacy issues, bias from algorithms, and over-personalization leading to user fatigue. The paper mentions the opportunities and challenges it provides to AI regarding social media, the potential impact of AI on social media in reshaping the digital landscape, and how far AI has transformed social media into an advanced technology.